Stimulatory effect of Eucalyptus essential oil on innate cell-mediated immune response - Serafino, Annalucia (BioMed Central, 2008)
BACKGROUND: Besides few data concerning the antiseptic properties against a range of microbial agents and the anti-inflammatory potential both in vitro and in vivo, little is known about the influence of Eucalyptus oil (EO) extract on the monocytic/macrophagic system, one of the primary cellular effectors of the immune response against pathogen attacks. The activities of this natural extract have mainly been recognized through clinical experience, but there have been relatively little scientific studies on its biological actions. Here we investigated whether EO extract is able to affect the phagocytic ability of human monocyte derived macrophages (MDMs) in vitro and of rat peripheral blood monocytes/granulocytes in vivo in absence or in presence of immuno-suppression induced by the chemotherapeutic agent 5-fluorouracil (5-FU). METHODS: Morphological activation of human MDMs was analysed by scanning electron microscopy. Phagocytic activity was tested: i) in vitro in EO treated and untreated MDMs, by confocal microscopy after fluorescent beads administration; ii) in vivo in monocytes/granulocytes from peripheral blood of immuno-competent or 5-FU immuno-suppressed rats, after EO oral administration, by flow cytometry using fluorescein-labelled E. coli. Cytokine release by MDMs was determined using the BD Cytometric Bead Array human Th1/Th2 cytokine kit. RESULTS: EO is able to induce activation of MDMs, dramatically stimulating their phagocytic response. EO-stimulated internalization is coupled to low release of pro-inflammatory cytokines and requires integrity of the microtubule network, suggesting that EO may act by means of complement receptor-mediated phagocytosis. Implementation of innate cell-mediated immune response was also observed in vivo after EO administration, mainly involving the peripheral blood monocytes/granulocytes. The 5-FU/EO combined treatment inhibited the 5-FU induced myelotoxicity and raised the phagocytic activity of the granulocytic/monocytic system, significantly decreased by the chemotherapic. CONCLUSION: Our data, demonstrating that Eucalyptus oil extract is able to implement the innate cell-mediated immune response, provide scientific support for an additional use of this plant extract, besides those concerning its antiseptic and anti-inflammatory properties and stimulate further investigations also using single components of this essential oil. This might drive development of a possible new family of immuno-regulatory agents, useful as adjuvant in immuno-suppressive pathologies, in infectious disease and after tumour chemotherapy.